Abiotic reductive removal of organic contaminants catalyzed by carbon materials: A short review. (12th August 2021) - Qin, Hejie; Sun, Yuankui; Rao, Dandan; Qiao, Junlian
Abstract: Since the observation that carbon materials can facilitate electron transfer between reactants, there is growing literature on the abiotic reductive removal of organic contaminants catalyzed by them. Most of the interest in these processes arises from the participation of carbon materials in the natural transformation of contaminants and the possibility of developing new strategies for environmental treatment and remediation. The combinations of various carbon materials and reductants have been investigated for the reduction of nitro‐organic compounds, halogenated organics, and azo dyes. The reduction rates of a certain compound in carbon‐reductant systems vary with the surface properties of carbon materials, although there are controversial conclusions on the properties governing the catalytic performance. This review scrutinizes the contributions of quinone moieties, electron conductivity, and other carbon properties to the activity of carbon materials. It also discusses the contaminant‐dependent reduction pathways, that is, electron transfer through conductive carbon and intermediates formed during the reaction, along with possibly additional activation of contaminant molecules by carbon. Moreover, modification strategies to improve the catalytic activity for reduction are summarized. Future research needs are proposed to advance the understanding of reaction mechanisms and improve the practical utility of carbon material for water treatment. Practitioner points: Reduction rates of contaminants in carbon‐reductant systems and modification strategies for carbon materials are summarized. Mechanisms for the catalytic activity of carbon materials are discussed. Research needs for new insights into carbon‐catalyzed reduction are proposed. Abstract : Electron transfer from reductants to organic contaminants catalyzed by carbon materials.